Pedagogical Content Knowledge (PCK) Representation in Vibration and Wave Teaching for Junior High School - Endang Purwaningsih (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
Learning materials of vibrations and waves in physics involve abstract mathematical knowledge, not easy to be understood, and frequently generate misconceptions. However, the subject is fundamental prerequisite for mastering more complicated physical concepts. On the other hand, teachers´ materials comprehension itself can affect the way teachers teaching and giving learning experience to the students. Here, we use descriptive research to figure out teacher´s pedagogical content knowledge (PCK) representation during teaching and learning process of vibrations and waves for junior high school grade VIII. Four professional junior high school teachers were chosen as sample. The PCK representation was focused on the content representation (CoRe) which represents teachers´ materials comprehension and their special aspects. Data collections have been done by means documentation study, ongoing classroom activities observation and interviews with the teachers as well as the students. Outcome of this research are: 1) Basic ideas/concepts expected by teachers for students to learn are not yet covering the basic concept needed to understand the concept itself, 2) Teachers are not yet mastering the teaching materials comprehensively, 3) Classroom activities/learning experiences and the method given to the students are not varied.